Performances da Pedagogia: uma narrativa estético-pedagógica / Performances of Pedagogy: anaesthetic-pedagogical narrative - Lombardi, Lucia Maria Salgado dos Santos (Educar em Revista, 2018)
O artigo analisa questões que têm emergido de experimentações feitas no cruzamento da formação de professores e da arte da performance no contexto de um curso de Pedagogia. A linguagem performática é abordada em suas dimensões expressiva e formativa, ampliando os horizontes das reflexões sobre as culturas escolares, as relações pedagógicas e as intencionalidades do ato educativo. Para construir o debate, a narrativa é estruturada de forma a revelar as etapas de trabalho de três iniciativas performativas, analisando-as. * * * The article analyzes questions that have emerged from the experiments carried out at the intersection of teacher training and performance art in the context of a Pedagogy course. The performance language is approached in its expressive and formative dimensions, broadening the horizons of reflections on school cultures, pedagogical relationships and the intentionalities of the educational act. In order to construct the debate the narrative is structured in order to reveal the stages of work of three performative initiatives, analyzing them.